Efficiency in functional analysis of problem behavior: A quantitative and qualitative review. Issue 1 (4th June 2019) - Saini, Valdeep; Fisher, Wayne W.; Retzlaff, Billie J.; Keevy, Madeleine
Abstract : Originating in the mid‐1960s, functional analysis (FA) has become the gold standard method for understanding the environmental variables that come to shape and maintain problematic behaviors such as aggression, self‐injury, and property destruction. Over the decades, a number of studies have refined FA methods, attempting to improve the overall efficiency of the analysis through experimental design and procedural modifications. In the present review, we used ongoing visual‐inspection criteria and basic probability theory to compare and analyze levels of efficiency across FA types. The multielement design and synthesized contingency analyses were about equally efficient with respect to the mean number of sessions conducted per function tested, and the trial‐based and synthesized contingency analyses were the 2 most efficient with respect to the mean duration per function tested. We discuss the implications of these findings in the broader context of efficiency and provide recommendations for maximizing efficiency during an FA. We also discuss other qualitative procedural details that may influence the overall efficiency of an FA.